2012
DOI: 10.1080/02786826.2012.683204
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distributions following Condensational Growth in Continuous Flow Aerosol Reactors as Derived from Residence Time Distributions: Theoretical Development and Application to Secondary Organic Aerosol

Abstract: Condensational growth in continuous flow reactors, such as continuously mixed flow reactors (CMFRs) and flow tube reactors, is widely employed in the field of aerosol science and technology to produce particles for industrial use and scientific research. The development of analytical equations for the number-diameter distribution n(d) of the particles in the outflow from these reactors is advantageous both for the inversion of data sets to obtain thermodynamic and kinetic parameters as well as for the rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 41 publications
1
46
0
Order By: Relevance
“…In the reaction chamber, the oxidized precursor was condensed onto the seed particles, resulting in a size distribution characteristic of a continuous reactor (Kuwata and Martin 2012). After a period of about 12 h to allow the smog chamber and aerosol production to stabilize, measurements were started.…”
Section: Methodsmentioning
confidence: 99%
“…In the reaction chamber, the oxidized precursor was condensed onto the seed particles, resulting in a size distribution characteristic of a continuous reactor (Kuwata and Martin 2012). After a period of about 12 h to allow the smog chamber and aerosol production to stabilize, measurements were started.…”
Section: Methodsmentioning
confidence: 99%
“…Additional considerations related to the physical interpretation of terms λ and β are discussed in Seinfeld et al (2003) and Kuwata and Martin (2012). These studies have shown that even with the myriad compounds of secondary organic aerosol, the number-diameter distributions of actual data sets, such as those of α-pinene or β-caryophyllene ozonolysis, are adequately represented by…”
Section: Condensational Growth Ratementioning
confidence: 99%
“…Kuwata and Martin (2012) previously compared the number-diameter distributions obtained by Equations (4) and (6) to observed distributions exiting the Harvard Environmental Chamber. The model was based on condensational growth described by Equations (6) and (7) in a CMFR (Seinfeld et al 2003;Kuwata and Martin 2012).The model could describe the data for secondary organic material produced by ozonolysis of α-pinene and β-caryophyllene. The interpretation is that condensational growth can be considered as the principal mechanism for change in particle diameter in these experiments.…”
Section: Linearly Segmented Distributionmentioning
confidence: 99%
See 2 more Smart Citations